Improved Sampled Average Modulation Technique for the Modular Multilevel Converters - Juan Carlos Colque; Ernesto Ruppert Filho; José Luis Azcue (Energies, 2022)
In this article the improved sampled average modulation technique is proposed, this technique has 2N + 1 levels in the output voltage waveform of MMC and it is considered as of low complexity of implementation for any number of submodules per arm. For that, characteristics such as dynamic response, implementation complexity, inverter output voltage waveform levels, and switching frequency are considered to evaluate and validate the proposed modulation technique. The proposed technique is compared with other three previously proposed techniques, its considering parameters such as the THD and the fundamental value of the output voltage, and also the peak-to-peak variation of the submodule capacitor voltage. Several simulations were performed in the Matlab/Simulink software and with these results, it was validated the proposed modulation technique, and also it is verified that the proposed technique is computationally more efficient. This last one shows its potential for multiphase multilevel applications.